Perdamaian melalui Pendekatan Keadilan Restoratif dalam Penanganan Tindak Pidana Anak di Indonesia - Karen Howard Lalamentik; Ina Heliany (PT Elaborium Elevasi Indonesia, 2026)
Peace through the restorative justice approach emerged in Indonesian society following public attention to a juvenile criminal case involving the child of a well-known musician couple in a fatal traffic accident in 2013, which resulted in the deaths of seven people, as reflected in Decision No. 123/Pid.Sus/2014/PN.Jkt.Tim. Based on this background, this study formulates three main issues: the differences in legal processes between the application of restorative justice under PERPOL-RI No. 6 of 2019 and PERJA No. 15 of 2020 and the aforementioned case; the legal consequences experienced by children in conflict with the law in court decisions applying restorative justice-based settlements; and the conditions under which restorative justice can be successfully implemented in handling juvenile crimes within the Indonesian legal system. This research employs a normative juridical method with descriptive non-statistical analysis, utilizing secondary data consisting of primary, secondary, and tertiary legal materials. The findings indicate that the effectiveness of restorative justice depends on procedural compliance, victim participation, offender accountability, and institutional oversight. Therefore, consistent and selective implementation enables the achievement of substantive peace and holistic justice, although not all types of juvenile crimes can be resolved through this approach due to normative and contextual limitations within Indonesia’s criminal justice practice.